Peran Perempuan Bekerja Dalam Menunjang Perekonomian Keluarga Melalui Pendekatan Fiqih Perempuan: Studi Pada Karyawan Franchise Tom Pizza di Kota Jambi - Kurnia Ernisa; Ridhwan .; Aditya Pratama (JOURNAL OF SHARIA ECONOMICS, 2025)
The increasing participation of women in economic activities is driven by changes in societal concepts and attitudes, as well as ongoing improvements. Through active involvement in development, women are able to contribute to meeting their daily needs through their own income. This study aims to identify and analyze the factors that motivate women to work at the Tom Pizza franchise, as well as to examine the role of working women in improving family economic conditions through their employment at Tom Pizza. This research employs a qualitative approach, with informants consisting of eight Tom Pizza employees, the business owner, and gender studies experts. The findings reveal that female employees at Tom Pizza are motivated primarily by economic factors, namely to help fulfill household needs, as well as by needs for self-actualization and social interaction. From the perspective of Islamic jurisprudence (fiqh al-nisa’), their employment is considered permissible (mubah) as long as it adheres to Islamic principles, such as maintaining personal dignity, obtaining spousal consent (for married women), and not neglecting domestic responsibilities. The study also highlights that women's involvement in the labor market significantly contributes to household economic stability and reflects a broader shift from traditional domestic roles to active public participation.These findings imply the importance of gender-sensitive policies and the need for a more contextual and adaptive interpretation of fiqh to align with contemporary social realities. This research is expected to serve as a reference for further studies on women, family economics, and Islamic commercial jurisprudence (women’s fiqh).